Control of Breathing in Ectothermic Vertebrates - Milsom, William K.; Gilmour, Kathleen M.; Perry, Steve; Gargaglioni, Luciane H. [UNESP]; Hedrick, Michael S.; Kinkead, Richard; Wang, Tobias (Wiley, 2022)
The ectothermic vertebrates are a diverse group that includes the Fishes (Agnatha, Chondrichthyes, and Osteichthyes), and the stem Tetrapods (Amphibians and Reptiles). From an evolutionary perspective, it is within this group that we see the origin of air-breathing and the transition from the use of water to air as a respiratory medium. This is accompanied by a switch from gills to lungs as the major respiratory organ and from oxygen to carbon dioxide as the primary respiratory stimulant. This transition first required the evolution of bimodal breathing (gas exchange with both water and air), the differential regulation of O2 and CO2 at multiple sites, periodic or intermittent ventilation, and unsteady states with wide oscillations in arterial blood gases. It also required changes in respiratory pump muscles (from buccopharyngeal muscles innervated by cranial nerves to axial muscles innervated by spinal nerves). The question of the extent to which common mechanisms of respiratory control accompany this progression is an intriguing one. While the ventilatory control systems seen in all extant vertebrates have been derived from common ancestors, the trends seen in respiratory control in the living members of each vertebrate class reflect both shared-derived features (ancestral traits) as well as unique specializations. In this overview article, we provide a comprehensive survey of the diversity that is seen in the afferent inputs (chemo and mechanoreceptor), the central respiratory rhythm generators, and the efferent outputs (drive to the respiratory pumps and valves) in this group. © 2022 American Physiological Society. Compr Physiol 12: 1-120, 2022.